Colleges and schools-Craig School of Business-Entrepreneurship-0012
Tony Eusz, mentor and Duniba High School Teacher helps students (foresound) Chris Ransel, Veronica Ochoa, Steve Luna, Paul Sigh with a business plan for the project called Coffee Shop.